Historia del pensamiento político griego : teoría y praxis - Barceló, Pedro, 1950-; Hernández de la Fuente, David A.; Roldán Hervás, José Manuel (Madrid : Editorial Trotta, 2014)
The object of this book is to analyze the genesis and development of political theory and praxis in ancient Greece, from the archaic period to the beginning of the Hellenistic era.
Esbozos políticos en los albores del mundo griego -- Concreciones políticas : polis, ethnos y basileia -- Crisis y consolidación de la polis (siglos VII-VI) -- Teoría y praxis políticas en la época clásica (siglo V) -- Teoría y praxis políticas en la transición al helenismo (siglo IV).
Includes bibliographical references and indexes.
Online resource; title from PDF title page (Digitalia, viewed April 15, 2019)
Keywords: Political science -- Greece -- History; Electronic books